NAFS PERSPEKTIF PEMIKIR ISLAM - Fathul Khair; Muhammad Amri; Indo Santalia (ADIBA : JOURNAL OF EDUCATION, 2023)
Man is a creature of God given by Him, reason and lust. Lust is an Islamic term used in the Quran and sunnah it becomes a term with a distinctive meaning of Islamic culture. To know the position of lust in the soul and its role in human life. Fitrah, Al-Iradah, Dhamir Qalb, Al-hawa lust often envelops the human heart, that is where man must seek good practices to combat the bad passions that are in his heart. Nafs are also referred to as souls. Many scholars such as Al-Ghazali and Ibn Taimiyah define the meaning of Nafs and also divide it into three parts namely, Nafs al-amarah, Nafs al-lawwamah, and finally Nafs al-mutmainnah. Qur'an, Nafs have different meanings. It can be as the self of God, the self or a person, as the spirit, as the soul, as the totality of man, and as the inner side of man that gives birth to behavior.